2003
DOI: 10.1002/eji.200323455
|View full text |Cite
|
Sign up to set email alerts
|

Critical role for OX40 ligand in the development of pathogenic Th2 cells in a murine model of asthma

Abstract: Bronchial asthma is characterized by massive infiltration of eosinophils and airway hyperreactivity (AHR), which are caused by overproduction of Th2 cytokines (IL-4, IL-5, and IL-13) by allergen-specific T cells. We recently demonstrated a critical contribution of OX40 ligand (OX40L) to the development of Th2-mediated experimental leishmaniasis. In this study, we have examined the role of OX40L in the development of Th2-mediated pulmonary inflammation by utilizing OX40L-deficient mice and a neutralizing anti-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 32 publications
5
90
1
Order By: Relevance
“…OX40L has been shown to induce Th2 skewing both in vitro (17,48) and in vivo (18,19) and mediates Th2 skewing induced by the thymic stromal lymphopoietin (TSLP) (20). We found a significant up-regulation of both Jagged-2 and OX40L expression by CD11c ϩ cells isolated from the MLN of CT-fed mice, specifically by CD103 ϩ cells.…”
Section: Discussionmentioning
confidence: 70%
“…OX40L has been shown to induce Th2 skewing both in vitro (17,48) and in vivo (18,19) and mediates Th2 skewing induced by the thymic stromal lymphopoietin (TSLP) (20). We found a significant up-regulation of both Jagged-2 and OX40L expression by CD11c ϩ cells isolated from the MLN of CT-fed mice, specifically by CD103 ϩ cells.…”
Section: Discussionmentioning
confidence: 70%
“…OX40L-deficient mice on C57BL/6 or BALB/c background were obtained from Drs. N. Ishii and K. Sugamura (Tohoku University School of Medicine, Sendai, Japan) (33,34). CD40-deficient mice on BALB/c background were gift from Dr. H. Kikutani (Osaka University, Osaka, Japan) (35).…”
Section: Micementioning
confidence: 99%
“…CD134 is expressed early after CD4 T cell activation and mediates induction of effector T cell differentiation (2)(3)(4). Recent reports have also shown that CD134 can costimulate T regulatory cells (5), influence bystanding cells, and also facilitate accumulation of effector T cells in pulmonary tissue (6,7). In much the same way, stimulation of CD137 induces very similar effects in populations of peptide-specific CD8 T cells (1,8,9).…”
mentioning
confidence: 99%